2021
DOI: 10.5194/tc-15-547-2021
|View full text |Cite
|
Sign up to set email alerts
|

Annual and inter-annual variability and trends of albedo of Icelandic glaciers

Abstract: Abstract. During the melt season, absorbed solar energy, modulated at the surface predominantly by albedo, is one of the main governing factors controlling surface-melt variability for glaciers in Iceland. Using MODIS satellite-derived daily surface albedo, a gap-filled temporally continuous albedo product is derived for the melt season (May to August (MJJA)) for the period 2000–2019. The albedo data are thoroughly validated against available in situ observations from 20 glacier automatic weather stations for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 62 publications
2
43
0
Order By: Relevance
“…Therefore, the mean of SMD standard deviation (s) of all MODIS albedo products was calculated and values exceeding 1.5 s (SMD > 4) and whose associated p-value ≤ 0.05 were considered outliers and rejected. The statistical test s was applied to establish thresholds for data selection in remote sensing [20,32,59,60].…”
Section: Albedo Filteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the mean of SMD standard deviation (s) of all MODIS albedo products was calculated and values exceeding 1.5 s (SMD > 4) and whose associated p-value ≤ 0.05 were considered outliers and rejected. The statistical test s was applied to establish thresholds for data selection in remote sensing [20,32,59,60].…”
Section: Albedo Filteringmentioning
confidence: 99%
“…A dominant component of this error has been found to be the failure of MODIS to completely eliminate the effects of clouds, e.g., thin clouds and cloud edges [20]. These artefacts create abrupt variations in the surface albedo time series [59], and introduce both overestimation errors, partially eliminated here with the elimination of albedo values greater than 0.84, and underestimation errors. It should be taken into account that the study area pixel is covered by snow all year round, which would not justify very low albedo values.…”
Section: Albedo Trendmentioning
confidence: 99%
“…Recent studies have shown that dust has substantial influence on the mass balance of VIC (Wittmann, et al, 2017). Local volcanic eruptions produce tephra and additional dust deposition that also lower the surface albedo (Gunnarsson et al, 2021). In the northern ablation zone of VIC, the lowest surface albedo observed by satellite imagery is less than 0.1, which was confirmed in situ (De Ruyter-de Wildt et al, 2004;Gascoin et al, 2017).…”
Section: Surface Albedo Parameterizationmentioning
confidence: 85%
“…These unexpected values are caused by the decreased incoming solar irradiance and the increased solar zenith angles that effectively lower the quality of albedo retrievals (Gunnarsson et al, 2021). However, the low-biased winter albedo has very little impact on ice melt due to the low winter air temperatures; a change in winter albedo from 0.1 to 0.8 increases winter melt by <10% over the whole VIC.…”
Section: Surface Albedo Parameterizationmentioning
confidence: 99%
“…As contemporary precipitation has remained mostly unchanged in Iceland, changes in glacier SMB are primarily driven by trends in atmospheric temperature, resulting in fluctuations of meltwater runoff (Björnsson et al., 2013). Superimposed on this, major volcanic eruptions cause high incidental SMB variability as a result of large‐scale deposition of dark tephra (ashes) on the brighter snow and ice that amplifies surface melt through a strong albedo effect (Björnsson et al., 2013; Box et al., 2012; Gascoin et al., 2017; Gunnarsson et al., 2021; Schmidt et al., 2017). Icelandic glaciers have been losing mass since their peak extent at the end of the Little Ice Age in the mid‐to‐late 1800s (Aðalgeirsdóttir et al., 2020), with accelerated mass loss following the recent rapid Arctic warming (Meredith et al., 2019).…”
Section: Introductionmentioning
confidence: 99%